Wideband dual‐element leaky‐wave antenna with constant gain and enhanced broadside radiation bandwidth using multilayered composite right/left‐handed substrate integrated waveguide. Issue 3 (14th November 2016) - Wu, Guo‐Cheng; Wang, Guang‐Ming; Gao, Xiang‐Jun; Liang, Jian‐Gang
Abstract: In this study, a wideband dual‐element leaky‐wave antenna (DE‐LWA) is proposed to achieve constant gain and wideband broadside radiation by using multilayered composite right/left‐handed substrate integrated waveguide. The proposed DE‐LWA consists of two leaky‐wave radiator elements which are with slanted and vertical interdigital fingers slot arrays. To verify the simulated results, the proposed DE‐LWA is fabricated and measured. The measured results are in good agreement with the simulated ones, indicating that the fabricated antenna obtains broadside gain of 12.5 dB with variation of 1.0 dB over the frequency range of 8.725‐9.25 GHz (5.84%). Moreover, the proposed DE‐LWA also can provides a beam scanning property from backward −80° to forward +80° over the frequency range from 7.4 to 12.7 GHz with a constant gain of more than 10 dB. Besides, the electromagnetic performances of this work are better than those of the recently reported similar work in the references.